Pengaruh Inovasi Produk, Kualitas Pelayanan Elektronik Dan Citra Merk Terhadap Peningkatan Kepuasan Pelanggan Muslim (Studi pad PT. Shantika Bangun Perkasa) - Burhan Syamhari (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze the effect of product innovation, electronic service quality and brand image on increasing customer satisfaction at PT. Shantika Bangun Perkasa, the research model used in this study is a multilevel structural model and the SEM (Structural Equation Modeling) analysis technique operated through the AMOS program is used to test the hypotheses proposed so that in this study a minimum of 100 respondents were used as samples in the study. . So that from the research results it can be stated that there is a positive and significant influence between product innovation and brand image, and there is a positive and significant influence on electronic service quality and brand image and there is a significantly positive influence on brand image in customer satisfaction, and there is a significant positive simultaneous effect on product innovation and also on electronic service quality in customer satisfaction.